A Survey On Safety Awareness Among Quarry Workers At East Cost Malaysia - Siti Hajar, A. A.; Ahmad Rasdan, Ismail; M. R., Abdul Hamid (AENSI Publishing, 2014)
Lack of safety awareness among quarry workers caused a number of accidents in quarry industries. The objective of this study is to reveal the awareness of quarry workers towards safety. A survey was distributed randomly among quarry workers at Pahang, Terengganu and Kelantan. The survey consist 6 questions regarding safety at workplace. Results revealed that there is 56.9% respondent agree and totally agree that the health and safety suggestion made was given consideration and used. As many as 79.3% respondent admitted that they obey all the safety rule stated at the workplace and 86.3% respondent said they always focus and give full attention during completing their task. 88% respondents agreed that all accident will be reported to responsible person while 77.6% respondents agree that all personal protective equipment will be used suitable with the task given and 86.2% respondents said they doing their task following the safe operation procedure that provided by the company.